Natural and Anthropogenic Source of Heavy Metals Pollution in the Soil Samples of an Industrial Complex; a Case Study - Maryam Mohammadi Roozbahani (Iranian Journal of Toxicology, 2015)
Background: Soil serves as a major reservoir for contaminants as it can bind to various chemicals. The aim of this study was to evaluate the levels of some metals (Cd, Cu, Fe and V) in soil samples collected from different stations of Ahvaz Industrial Complex II to determine the natural and anthropogenic contribution of metal in the soil. Methods: This was an experimental study that carried out in 2013. Soil samples were obtained from 9 stations and were subjected to bulk digestion and chemical partitioning. Concentrations of Cd, Cu, Fe and V in soil were determined by ICP-OES. Contaminant factor (CF) and geo-accumulation index (I-geo) were used to evaluate the soil pollution in the samples. ANOVA, Duncan Multiple Range and Pearson correlation coefficient matrix tests was used to analyze the data. Results: According to I-geo results, the soil samples of the Ahvaz Industrial Complex II could be classified as strongly to very strongly pollute for Cd and it was unpolluted to moderately pollute for Cu, Fe and V. The amount of anthropogenic pollution was more than that of natural sources and the anthropogenic order of metals pollution was Fe (88%)> Cu (83%)> Cd (75%)> V (61%). Conclusion: Metals concentrations are the highest at a distance of 300m from the pollution source. V, Cu and Cd pollutants are probably originated from oil industries.